Junior High School Science Teachers’ Perception of Their Technological Pedagogical Content Knowledge (TPACK) - Joseph Kobina Baah; Kofi Acheaw Owusu (Scientia Publica Media, 2025)
The integration of technology into education has become indispensable in fostering effective teaching and learning, particularly in the sciences. However, the ability of teachers to blend technological tools with pedagogical strategies and content knowledge is captured in a framework known as Technological Pedagogical Content Knowledge (TPACK). Despite the growing emphasis on technology in education, limited research exists on the TPACK competencies of science teachers in Ghana. Understanding these competencies is vital for informing professional development programs and enhancing the quality of science education in Junior High Schools (JHS). This study explored three main questions: (1) How do JHS science teachers perceive their understanding of TPACK constructs? (2) What are the correlations between these constructs, their collective impact on TPACK, and (3) what construct is the strongest predictor of TPACK? A descriptive survey design utilizing questionnaires to collect primary data from 145 JHS science teachers was employed. Data were analyzed using frequency distributions, means, standard deviations, and multiple regression. The findings revealed that science teachers demonstrate a high perceived understanding of the TPACK constructs. There were strong positive correlations between TPACK and its six constituent constructs. Notably, Technological Content Knowledge (TCK) emerged as the most significant predictor of overall TPACK competency. These results underscore the robust self-perceptions of TPACK competencies among JHS science teachers in the study area, suggesting a strong foundation for technology integration in science education. The study’s findings provide valuable insights for policymakers, educational administrators, and teacher educators in Ghana. The study recommends the development of targeted professional development programs in technology to strengthen teachers’ TPACK capacity to improve science education outcomes in Ghanaian junior high schools. Furthermore, the identification of TCK as a key predictor highlights the importance of focusing on the intersection of technology and content knowledge in teacher training initiatives.